Vitamin D in Corona Virus Disease 2019 (COVID-19) Related Multisystem Inflammatory Syndrome in Children (MIS-C) - Feketea, Gavriela; Vlacha, Vasiliki; Bocsan, Ioana Corina; Vassilopoulou, Emilia; Stanciu, Luminita Aurelia; Zdrenghea, Mihnea (Frontiers in Immunology, 2021)
Multisystem Inflammatory Syndrome in children (MIS-C) is a rare but devastating complication of coronavirus disease 19 (COVID-19). The development of prognostic biomarkers and more importantly the implementation of new treatment modalities would have a significant impact in clinical practice regarding the outcome of MIS-C. Vitamin D could be a potential candidate. In this mini review we analyze the immunomodulatory role of vitamin D in viral infections and specifically in COVID-19. We also examine the current literature regarding the association of vitamin D with MIS-C and Kawasaki disease. The vitamin D was evaluated not only as a biomarker but also as a nutritional supplement. We concluded that vitamin D levels could be valuable in predicting severe forms of MIS-C and correction of abnormal levels in severe MIS-C may influences its evolution. 25-hydroxyvitamin D3 [25(OH)D3] supplementation raising serum [25(OH)D] concentrations potentially have a favorable effect in reducing the severity of MIS-C in certain circumstances. Further studies are needed to confirm these results.